Kinetic energy storage using a dual-braking system for an unmanned parallel hybrid electric vehicle. (September 2017) - Suntharalingam, Piranavan; Economou, John T; Knowles, Kevin
In this paper a novel regenerative dual-braking strategy is proposed for utility and goods delivery unmanned vehicles on public roads, which improves their ability to recover regenerative energy and consequently improves the fuel use of parallel hybrid powertrain configurations for land unmanned vehicles where the priority is not comfort but extension of their range. Furthermore, the analysis takes into account the power-handling ability of the electric motor and the power converters. In previous research, a plethora of regenerative braking strategies have been reported; in this paper, the key contribution is that the vehicle electric regeneration is related to a fixed braking distance in relation to the energy storage capabilities specifically for unmanned utility-type land vehicles where passenger comfort is not a concern but pedestrian safety is of critical importance. Furthermore, the power converter capabilities of the vehicle facilitate the process of extending the braking time by introducing a variable-deceleration profile. The proposed approach has therefore resulted in a regenerative algorithm which improves the energy storage capability of the vehicle without considering the comfort since this analysis is applicable to unmanned vehicles. The algorithm considers the distance as the key parameter, which is associated with safety; therefore, it allows the braking time period to be extended, thus favouring the electric motor generation process while maintaining safety. This method allows the vehicle to brake for longer periods rather than for short bursts, hence resulting in more effective regeneration with reduced use of the dual system (i.e. the caliper–stepper motor brake system). The regeneration method and analysis are addressed in this paper. The simulation results show that the proposed regenerative braking strategy improved the ability of the hybrid powertrain configuration to recover energy significantly. The paper is also supported by experimental data that verify the theoretical development and the simulation results. The two strategies developed and implemented utilize a constant braking torque and a constant braking power. Both methods were limited to a fixed safety-based distance. Overall, the results demonstrate that the constant-braking-torque method results in better energy-based savings.